Systematic and Effective Change in HR Behaviour and Competencies Lead to Organizational Development (Global Journal of Management and Business Research, 2016)
In the era of globalization the markets and opportunities for more growth and revenues have increased. Today, teams and organizations face rapid change like never before. Organization required changing their current strategy or adopting the latest technology for better output and making an edge over their competitors. But due to implementation of new technology or strategy; there are some employees in the organization who react on the implementation; they won't be happy over the change. This paper explain if any organization wants to include any new technology in their daily work then there will be a big fix of understanding the core method coping with it. Employee will get confuse how to cope up that technology, it might be a machine newly included in the factory. The main objective of this paper is to find out the reaction after implementing new technology in Ready Made Garments (RMG) factory. If we put as an example then RMG sector is the best suited for this. In this sector managements always try to adopt a change in their technologies.
Keywords: globalization; growth; changing; strategy; technology; implementation; efficiency